2021
DOI: 10.1093/eurheartj/ehab433
|View full text |Cite
|
Sign up to set email alerts
|

Thin-cap fibroatheroma predicts clinical events in diabetic patients with normal fractional flow reserve: the COMBINE OCT–FFR trial

Abstract: Aims The aim of this study was to understand the impact of optical coherence tomography (OCT)-detected thin-cap fibroatheroma (TCFA) on clinical outcomes of diabetes mellitus (DM) patients with fractional flow reserve (FFR)-negative lesions. Methods and results COMBINE OCT-FFR study was a prospective, double-blind, international, natural history study. After FFR assessment, and revascularization of FFR-positive lesions, patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
119
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 171 publications
(125 citation statements)
references
References 31 publications
5
119
0
1
Order By: Relevance
“…The design of the COMBINE OCT-FFR trial 7 and the main results have been published previously. 6 In brief, the trial is a multi-center, prospective, natural history study which combined hemodynamic (by FFR) and morphological (by OCT) assessment of nonischemic lesions to better predict adverse events in patients with diabetes. The study population consisted of all patients with diabetes who underwent angiography for any indication and had at least one de-novo native coronary lesion with a diameter stenosis of 40% to 80% by visual assessment (other than the culprit lesion, if patients presented with myocardial infarction).…”
Section: Methodsmentioning
confidence: 99%
“…The design of the COMBINE OCT-FFR trial 7 and the main results have been published previously. 6 In brief, the trial is a multi-center, prospective, natural history study which combined hemodynamic (by FFR) and morphological (by OCT) assessment of nonischemic lesions to better predict adverse events in patients with diabetes. The study population consisted of all patients with diabetes who underwent angiography for any indication and had at least one de-novo native coronary lesion with a diameter stenosis of 40% to 80% by visual assessment (other than the culprit lesion, if patients presented with myocardial infarction).…”
Section: Methodsmentioning
confidence: 99%
“…The COMBINE OCT-FFR trial by Kedhi et al investigated the prognostic impact of the presence of a TCFA as identified with OCT in patients with diabetes mellitus [ 69 ]. From the total cohort of 550 patients, 25% had a hemodynamically insignificant TCFA (i.e., fractional flow reserve >0.80), and it was observed that these patients had a fivefold higher risk for adverse cardiac events within 18 months, consisting of cardiac mortality, target vessel myocardial infarction, target lesion revascularization, or unstable angina requiring hospitalization, compared with patients without TCFA.…”
Section: Intracoronary Imaging Modalitiesmentioning
confidence: 99%
“…The new generation of OCT integrates the detection function of FFR and obtains morphological and functional information at the same time. This achieves the guiding effect of optimizing the treatment of critical lesions ( 28 , 29 ).…”
Section: Oct Guides Interventional Coronary Artery Treatmentmentioning
confidence: 99%
“…With the continuous improvement of OCT, it is expected to have an important role in the examination of coronary intravascular lesions, the optimization of PCI strategies and the development of novel stents. The expected future development directions and advantages of OCT are listed below ( 29 , 74-78 ).…”
Section: Application Prospects Of Oct In the Field Of Cardiovascular ...mentioning
confidence: 99%